The post-industrial scenario: changes in the object environment, in contemporary society, and in its new paradigms - Dantas, Denise (Pós. Revista do Programa de Pós-Graduação em Arquitetura e Urbanismo da FAUUSP, 2007)
This article studies the social, cultural, and marketing relations of the object, identifying changes that have defined contemporary society based on a comparison between industrial society and post-industrial society, with particular emphasis on changes that interfere with the manufacturing of consumer goods. It provides a survey of the contemporary setting of material culture and considers changes taking place in everyday life and their organization, in the living space, and in social, production, and consumption relations that have affected the manufacturing of objects over the past 40 years.